Role of Middleware, Integration Platforms, and API Solutions in Driving Digital Transformation for Enterprises - Wairagade, Anant (Journal of Science & Technology, 2021)
Organizations in today’s digital environment must use advanced technological solutions that enable their operational functions, strategic initiatives, and customer engagement processes. Strong businesses that aim to stay competitive in digital worldwide systems need digital transformation as their key survival requirement (Trakadas et al., 2019). Interoperable communication depends on middleware technologies that use integration platforms and APIs to enable better data administration and flexible business procedures (Forcadell et al., 2019). This paper investigates the elements that support digital transformation and their impact on enterprise accomplishments.